2011
DOI: 10.1161/circulationaha.110.990549
|View full text |Cite
|
Sign up to set email alerts
|

Increased Vertebral Artery Tortuosity Index Is Associated With Adverse Outcomes in Children and Young Adults With Connective Tissue Disorders

Abstract: Background-Arterial tortuosity is described as a common and distinctive feature of Loeys-Dietz syndrome (LDS), yet reports on arterial tortuosity are based on qualitative observations and none have investigated an association between tortuosity and cardiovascular outcomes in LDS or other connective tissue disorders. Methods and Results-We performed a retrospective analysis of 90 patients Յ50 years of age with Marfan syndrome, LDS, Ehlers-Danlos syndrome, or nonspecific connective tissue disorder who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
175
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(197 citation statements)
references
References 21 publications
14
175
0
8
Order By: Relevance
“…The patients with DPLI in the present study also showed a significantly higher percentage of unilateral dominance. The vertebral artery is reported to be significantly associated with the size of the transverse foramina 12) and its tortuosity is associated with adverse outcomes in young patients with connective tissue disorders 13) . However, there have been no previous studies regarding the differences in the confluent angles between the terminal portion of the vertebral artery and the proximal portion of the BA.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with DPLI in the present study also showed a significantly higher percentage of unilateral dominance. The vertebral artery is reported to be significantly associated with the size of the transverse foramina 12) and its tortuosity is associated with adverse outcomes in young patients with connective tissue disorders 13) . However, there have been no previous studies regarding the differences in the confluent angles between the terminal portion of the vertebral artery and the proximal portion of the BA.…”
Section: Discussionmentioning
confidence: 99%
“…5 To refine medical and surgical guidelines for managing patients with CTDs, novel indicators of vascular phenotype severity such as aortic stiffness and vertebral tortuosity index have been proposed. 6,7 CTD patients are known to have structural changes within the aortic wall including degeneration of elastic fibers, increased collagen content, and smooth muscle cell loss. These changes result in increased aortic wall stiffness, which has been demonstrated by using cardiac MRI (CMR) and other techniques.…”
mentioning
confidence: 99%
“…Such a vascular anomaly might be at risk of iatrogenic injury during manual therapy, trauma, positioning for surgery and removal of tumours at the base of the skull. Indeed, a previous study showed that tortuosity of the VA is associated with increased risk of arterial dissection and iatrogenic injury [9].…”
Section: Discussionmentioning
confidence: 99%